Aerator Usage in Typical Nile Tilapia Farms in Northeastern Thailand: A Study in the Context of Climate Change - Rangsiwiwat, Amornrat; Harnmontri, Ruengrit; Lebel, Boripat; Lebel, Phimphakan; Lebel, Louis; Lamkom, Thanathip; Jutagate , Achara; Jutagate, Tuantong (Journal of Fisheries and Environment, 2025)
This study highlights the role of aerator usage in tilapia farming under climate-related challenges, by interviewing the fish farmers about their experience in extreme weather and climate-risk events and examining the factors influencing the adoption of aerators. A survey of 530 tilapia farmers across six provinces in Northeastern Thailand was conducted to assess aerator usage and the impact of climate-related events. About two-thirds of the interviewees were men, over half were aged 50 or more, and the majority, two-thirds, had a primary education level. Cage culture in reservoirs was the most common system, followed by cages in rivers and ponds. Four types of aerators, fountain, diffuser, paddlewheel, and venturi were identified across various aquaculture systems. Regression tree analysis revealed that aerator use was influenced by age and education of the farmers, additional factors included fish release size, aquaculture system, feed conversion rate, and stock density. Logistic regression analysis identified the significance of each factor influencing aerator use. The results showed that older farmers were less likely to adopt aerators, whereas larger fish, reservoir cages, higher farmers’ education, and improved FCR increased the likelihood of aerator usage (p<0.05). Despite only 20% of farmers using aerators, many acknowledged their potential to reduce fish mortality and improve yields, especially during extreme heat events. The study recommends promoting efficient aerator practices, optimizing their placement, and introducing targeted educational programs to strengthen climate resilience in tilapia farming.